ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI TIDAK BERFUNGSINYA TERMINAL BIREUEN - Alwin Rusydi; Muhammad Isya; Yusria Darma (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
Bireuen Terminal is a Type B Terminal located in Geulumpang Payong Village, Jeumpa District, Bireuen Regency. The existence of the Bireuen Terminal has not been functioned optimally, due to the lack of activity that occurs in the terminal environment. In addition, the presence of a shadow terminal is also one of the causes of the lack of activity in the terminal. This research aims to investigate factors that affect the malfunctioning of Bireun terminal. This research was carried out by making direct observations at the research site and also distributing questionnaires to research informants consisting of the Aceh Provincial Transportation Office as well as Organda and DPRK Bireuen. Selection of informants (key persons) using purposive sampling techniques. Data analysis uses the Process Hierarchy Analysis (AHP) method with criteria, namely: road service level, accessibility, terminal facilities and management, environmental comfort and environmental safety. The results of the analysis show that the Bireuen Terminal has not met the requirements as a Type B Terminal. The main factors affecting the malfunctioning of the Bireuen Terminal were obtained from the accessibility criterion with a weight value of 0.327, the facility and terminal management criteria with a weight value of 0.307, the road service level criterion with a weight value of 0.157, the environmental safety criterion with a weight value of 0.113 and the environmental comfort criterion with a weight value of 0.100. The first alternative that needs to be optimized so that Bireuen Terminal works again, is the alternative location of the terminal that is easy to reach which is contained in the accessibility criteria, which indicates that this alternative is the most important alternative compared to other alternatives. Followed by alternative facilities in the terminal are adequate which are contained in the criteria for facilities and terminal management.